2011
DOI: 10.5090/kjtcs.2011.44.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Results of Extracorporeal Membrane Oxygenation (ECMO) Support before Coronary Reperfusion in Cardiogenic Shock with Acute Myocardial Infarction

Abstract: BackgroundDespite aggressive treatment, the mortality rate of cardiogenic shock with acute myocardial infarction (AMI) is high. We performed extracorporeal membrane oxygenation (ECMO) prior to coronary reperfusion, and evaluated the early clinical results and risk factors.Materials and MethodsFrom May 2006 to November 2009, we reviewed the medical records of 20 patients in cardiogenic shock with AMI (mean age 67.7±11.7 yrs, M : F 14 : 6). After initially performing ECMO using the CAPIOX emergency bypass system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…This is in contrast with previous studies that have identified various predictive factors of in-hospital mortality. 6,8,9,11,13,15,16,28 Our subgroup analyses highlighted a survival advantage only in patients aged ≤60 years. Muller et al identified pre-ECLS age >60 years as an independent predictor of intensive care unit death in one of the largest published series of ECLS support for cardiogenic shock in the setting of AMI.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is in contrast with previous studies that have identified various predictive factors of in-hospital mortality. 6,8,9,11,13,15,16,28 Our subgroup analyses highlighted a survival advantage only in patients aged ≤60 years. Muller et al identified pre-ECLS age >60 years as an independent predictor of intensive care unit death in one of the largest published series of ECLS support for cardiogenic shock in the setting of AMI.…”
Section: Discussionmentioning
confidence: 71%
“…26 Our results are consistent with previous articles that reported survival rates after ECLS for AMI complicated by cardiogenic shock comprised between 33 and 66%. [5][6][7][8][9][10][11][12][13][14][15][16] Preliminary data identified ECLS support for primary PCI as a significant contributor to the reduction of in-hospital mortality in patients with cardiogenic shock due to AMI. 5 The ideal timing--before or after primary PCI--of ECLS implantation in STEMI patients developing cardiogenic shock is still matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the largest observational studies, mean ECMO support was 4.7 days [ 9 ], which was far below the ECMO duration in our patient. Furthermore, longer ECMO support time is one of the risk factors of mortality [ 10 ], which may just reflect the poorer haemodynamic condition of the patient. On the other hand, ECMO does have an inherent myriad of possible complications, which can be machine-related or patient-related.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Chung et al, of 134 CS patients recruited for ECMO, 50% were weaned and 42.5% survived to discharge. 58 In another study by Hei et al, 76% were weaned off ECMO and 63% survived to discharge. 59 In the study by Loforte et al, there were 47 survivors of 73 CS patients and 45% survived to discharge.…”
Section: Mechanical Circulatory Supportmentioning
confidence: 96%